Large-scale testing of bridge system with unseating mitigation devices under spatially varying ground motions - Shrestha, B.; Hao, Hong; Bi, Kaiming; He, L.; Ren, W. (2017)
This paper presents large-scale shake table experiments carried out to identify the effects of spatially varying ground motions on the response of bridge segments. A shake table array system with two independent shake tables was used to simulate non-uniform ground motions. Bridge model, scaled to 1:6, having two frames of length 8.33 m each was tested with and without the restraining devices. The frames designed to have the fundamental period close to each other as recommended by prevailing bridge codes were tested to stochastically simulated bi-directional spatially varying ground motions. Experiments were also conducted on second bridge model with Superelastic Shape Memory Alloy (SMA) restrainers used to mitigate the large relative displacements at the bridge joint. The results show that spatially varying ground motions could lead to damaging pounding even when the fundamental period of adjacent frames are close to each other.